1991
DOI: 10.1152/ajpgi.1991.261.5.g827
|View full text |Cite
|
Sign up to set email alerts
|

Profound increase in viscosity and aggregation of pig gastric mucin at low pH

Abstract: Epithelial mucins are glycoproteins of very large molecular weight that provide viscoelastic and gel-forming properties to mucus, the jellylike protective layer covering epithelial organs. In the mammalian stomach the mucus gel layer protects the underlying epithelial cells from HCl in the lumen. We report here that pig gastric mucin undergoes a 100-fold increase in viscosity in vitro when pH is lowered from 7 to 2. Sedimentation velocity and dynamic light-scattering measurements revealed the formation of extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
136
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 0 publications
19
136
0
Order By: Relevance
“…It has been previously reported that the presence of salts impacts mucin rheology. 8,31,32 The data presented in Figure 3 demonstrate that, as the salt concentration is increased at pH 2, PGM remains a gel up to a NaCl concentration of 100 mM, but the sample at 200 mM becomes a solution. At these very high salt concentrations PGM is a solution regardless of pH; however, even the 200 mM sample does cross over to a more solidlike response at high frequencies as is typical for a polymeric liquid.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been previously reported that the presence of salts impacts mucin rheology. 8,31,32 The data presented in Figure 3 demonstrate that, as the salt concentration is increased at pH 2, PGM remains a gel up to a NaCl concentration of 100 mM, but the sample at 200 mM becomes a solution. At these very high salt concentrations PGM is a solution regardless of pH; however, even the 200 mM sample does cross over to a more solidlike response at high frequencies as is typical for a polymeric liquid.…”
Section: Resultsmentioning
confidence: 96%
“…However, to the best of our knowledge, detailed bulk rheology experiments to study the impact of pH on the mechanical properties of gastric mucin have not been carried out. Previous work using falling ball viscometry 8 has shown that there is a profound increase in the apparent viscosity at low pH, though these experiments were not able to probe different shear rates and measure the full frequency-dependent linear viscoelastic moduli. Another study, in which the viscosity of partially purified PGM purchased from Sigma Chemicals with added trefoil peptides was examined, did note an increase in viscosity at low pH, although pH dependence in purified mucin was not studied.…”
Section: Introductionmentioning
confidence: 98%
“…Whether this is also true for airway surface liquid is still controversial (13,14), but recent measurements of the pH and HCO 3 Ϫ concentration of fluid secreted by polarized human submucosal gland cells, Calu-3, indicate that these cells are capable of secreting substantial amounts of HCO 3 Ϫ (ϳ80 mM) under appropriate stimulation, a process that would be defective in CF (15). An acidic luminal environment affects the physical properties of mucus (16,17) and promotes bacterial binding to mucins (18,19), both of which may have important implications for CF lung disease (20). As many CF-affected epithelia normally secrete substantial amounts of HCO 3 Ϫ , the luminal HCO 3 Ϫ concentration will vary under different physiological situations.…”
mentioning
confidence: 99%
“…Further polymerization leads to polymers with molecular weight ranging from 2 to 20 million Da, of which 70-80% is sugar. These polymers further aggregate, and, in the case of the gastric mucin, gel under acidic pH [5][6][7], and protect the stomach from autodigestion [8].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, Bansil, Turner et al [1,[5][6][7]9] examined the gelation of gastric mucin at acidic pH values using light scattering, fluorescence binding, atomic force microscopy, and rheology. For gastric mucin gels below pH = 4, these experiments showed that enzymatic or biochemical disruption of the non-glycosylated regions of PGM prevents gelation and that hydrophobic regions exposed at low pH are involved in gelation, suggesting that gelation of PGM involves the association of the non-glycosylated regions of the glycoprotein [1], via a complex interplay between hydrophobic association and electrostatic interactions of charged amino acids.…”
Section: Introductionmentioning
confidence: 99%